PESTLE Analysis of Production Management Landing Platform Dock Warship PT PAL Indonesia (Persero) For National Defense - Sarjito, Aris (Advances in Social Sciences Research Journal, 2020)
ABSTRACT Purpose: The purpose of this study is to analyze the production management of PT PAL Indonesia (Persero) ’s LPD vessel using PESTLE analysis. Study Design: This research is descriptive and uses a qualitative approach. Methodology: This study uses a qualitative analysis approach aimed at PT PAL Indonesia (Persero) ’s LPD ship production management. Place and Duration of Study: This research was conducted in Jakarta and Surabaya in August - October 2020. Results: (1) PT PAL Indonesia (Persero) is a strategic industry that produces the main equipment of the Indonesian defense system, especially for the marine dimension, (2) the Indonesian Navy relies on PT PAL Indonesia (Persero) to produce LPD-type vessels which are very important to implement sea ​​operations, (3) PT PAL Indonesia periodically measures the implementation and implementation of GCG, as regulated in the Regulation of the Minister of State for SOEs, (4) PT PAL Indonesia (Persero) collaborates with financial institutions and consultants to provide a funding scheme from the capital structure of soft loan provision , insurance and other forms of funding, (5) In the field of general engineering, companies make heavy industrial components such as power plants, diesel engines, steel structures, such as oil and gas industrial equipment, (6) PT PAL Indonesia (Persero) continuously improve the quality of technology and ensure that the products built follow state-of-the-art developments technology, and (7) PT PAL Indonesia (Persero) always strives to provide benefits to society by implementing real corporate social responsibility for the development of harmonious relationships with the community through Corporate Social Responsibility (CSR). Keywords: economy, environment, legal, political, sociocultural, technology